Effect of taper modification on the performance of NREL VI wind turbine blade for low and mid wind speeds. Issue 4 (August 2019) - Kaya, Mustafa; Elfarra, Munir
The taper distribution along the span of the NREL phase VI rotor blade is modified using a new approach. The taper distribution in this approach is expressed as a cubic spline defined by three chord lengths values in the spanwise direction: root, mid-span and tip. Then, the effect of the modified taper distribution on the thrust and the torque is studied. Various blade geometries are generated using different chord length values on the root, mid-span and tip locations while the planform area is kept fixed as the original blade, NREL VI. The flowfields are calculated using a commercial Reynolds averaged Navier–Stokes solver. The k-epsilon turbulence model is used to calculate the eddy viscosity. The computations are carried out for three different wind speeds: 5, 7 and 9 m/s. Increasing torque and decreasing thrust cases are observed. It is noticed that torque increases when the tip chord length is about one-fifth of the root and mid-span chord lengths. The thrust is decreased, as the root chord is much longer than the mid-span and the tip chord.